2017
DOI: 10.1177/0049475517699718
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus prevalence in rural areas in south-west Chad

Abstract: In Chad, hepatitis B virus (HBV) is thought to have a high prevalence and is consequently responsible for numerous acute and long-term complications. It is often detected during screening in potential blood donors. However, no general population-based study on the prevalence of hepatitis B has been performed. The aim of this study was to gain an impression of the HBV prevalence in rural areas in south-west Chad. A total of 1309 individuals (745 boys/men, 564 girls/women) with a median age of 15 years (age rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…Pregnant women with history of blood transfusion had a high chance of 18 times (40%; OR=17.9 95%CI: 2.6-124.8; P=0.01) to be infected by HIV. The similar result have been reported in Cameroon by 21 among pregnant women who had a history of blood transfusion (OR: 11; 1.60-75.50; p=0.03). This result could be explained to the fact that, blood is transfused to pregnant women to replace blood lost during labor and prevent maternal mortality.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Pregnant women with history of blood transfusion had a high chance of 18 times (40%; OR=17.9 95%CI: 2.6-124.8; P=0.01) to be infected by HIV. The similar result have been reported in Cameroon by 21 among pregnant women who had a history of blood transfusion (OR: 11; 1.60-75.50; p=0.03). This result could be explained to the fact that, blood is transfused to pregnant women to replace blood lost during labor and prevent maternal mortality.…”
Section: Discussionsupporting
confidence: 88%
“…13,20 In comparison to other studies carried out in Cameroon, similar finding of HBV and HIV seroprevalence among pregnant women were reported by. 21,22 The seroprevalence of HBV observed in our study reflects the overall prevalence of HBV in the general population in Chad (12%) 12 and the large gap with HIV seroprevalence could be explained by the fact that it is known that HBV is 50 to 100 times more contagious than HIV. 23 Indeed, HBV has been found in virtually all body secretions/excretions and unlike HIV, it can survive outside the body for at least 7 days after which the virus can still cause infection.…”
Section: Discussionsupporting
confidence: 55%
“…To note, previous studies targeting HIV-infected individuals and populations have shown that among HIV-infected individuals in N'Djamena, 13.5% were infected with HBV [36]. This HIV+HBV+ seroprevalence was similar to our results but lower than the rate of 22.9% obtained in the population of Southern Chad [37]. These geographic and temporal variations in prevalence could be related to differences in the number of samples analyzed and the type of patients sampled that are rarely representative of the same population and that dependent of population clusters.…”
Section: Discussionsupporting
confidence: 89%
“…Estimates of the prevalence of the virus in the population may also vary depending on gender and age, which indicates the need for careful analysis and selection of the groups to be examined. For instance, in rural areas of the southwestern Chad, the overall HBsAg+ prevalence was 22.9%, with the youngest age group (6-15 years) and boys/men showing significantly higher HBsAg prevalence than older groups and girls/women, respectively (p<0.01) [2]. Such significant differences among different groups may be caused by the development and implementation of new methods for HBV marker identification, although, according to some authors, the heterogeneity of the results obtained by different researchers in the same country is primarily associated with differences in geographic regions, socialization and introduction of universal immunization rather than with the patient's gender, HBV screening instrumentation and methodological characteristics of assays [6].…”
mentioning
confidence: 99%
“…There is a wide variation in HBsAg prevalence estimates in these countries. The highest prevalence of the virus has been found in sub-Saharan Africa, in such West African countries as Liberia (17.55%), Mali (15.5%), Burkina Faso (14.5%), Ghana (13.8%), Senegal (13.8%), Nigeria (13.6%), and Mauritania (10.9%) [2,3]. In East and South Africa, the HBsAg prevalence is relatively low and corresponds to the average level [1], whereas in such North African countries as Tunisia, Algeria, Egypt, and Morocco, the level is below 2% [4].…”
mentioning
confidence: 99%